2007
DOI: 10.1097/qad.0b013e328270388a
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal contraceptive use, herpes simplex virus infection, and risk of HIV-1 acquisition among Kenyan women

Abstract: In this group of high-risk African women, hormonal contraception and HSV-2 infection were both associated with increased risk for HIV-1 acquisition. HIV-1 risk associated with hormonal contraceptive use was not related to HSV-2 serostatus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
142
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(149 citation statements)
references
References 33 publications
6
142
1
Order By: Relevance
“…Our finding is however in agreement with another study report from Kenya [35]. Misguided confidence in the protective role of hormonal contraceptives may explain the significantly increased prevalence of HSV-2 among hormonal contraceptive users in this study.…”
Section: Discussionsupporting
confidence: 38%
“…Our finding is however in agreement with another study report from Kenya [35]. Misguided confidence in the protective role of hormonal contraceptives may explain the significantly increased prevalence of HSV-2 among hormonal contraceptive users in this study.…”
Section: Discussionsupporting
confidence: 38%
“…7 In South Africa, hormonal contraceptives, particularly injectables, are reported to be the most common contraceptive method because they are highly effective and safe. [8][9][10] Contraceptives play a key role in efforts to prevent HIV-1 infection by reducing the number of unintended pregnancies and, hence, the number of potential cases of motherto-child transmission of HIV-1.…”
Section: Introductionmentioning
confidence: 99%
“…In light of multiple studies implicating hormonal contraception use with increased susceptibility to HIV-1 infection [5][6][7][8][9][10][11] , identifying safe and effective contraceptives is a critical public health issue 4 . This study examined alterations to systemic and local immune mediators associated with extended use of hormonal contraception in order to delineate biological mechanisms that may affect the susceptibility to HIV-1 and other sexually transmitted diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Areas with high use of injectables often overlap with areas of high HIV-1 incidence, particularly in eastern and southern Africa 3 . Unfortunately, several studies have suggested that the use of hormonal contraceptives, particularly DMPA, is associated with an increased risk of acquiring and transmitting HIV-1 [4][5][6][7][8][9][10] . A recent observational study among HIV-1 serodiscordant couples indicated that the risk of acquiring HIV-1 was increased 2 to 3.9-fold in women using DMPA compared to non-hormonal contraception users 6,11 .…”
Section: Introductionmentioning
confidence: 99%